DISCUSSION OF THE STATE AND PERSPECTIVES OF DEVELOPMENT OF THERMAL PROCESSING OF (Α+Β)-TITANIUM ALLOYS - V. N. Fedulov (Литьë и металлургия)
The perspectives of development of thermal treatment of α + β-titanium alloys are examined.